2020
DOI: 10.1371/journal.pone.0229468
|View full text |Cite
|
Sign up to set email alerts
|

Triploidy in zebrafish larvae: Effects on gene expression, cell size and cell number, growth, development and swimming performance

Abstract: There is renewed interest in the regulation and consequences of cell size adaptations in studies on understanding the ecophysiology of ectotherms. Here we test if induction of triploidy, which increases cell size in zebrafish (Danio rerio), makes for a good model system to study consequences of cell size. Ideally, diploid and triploid zebrafish should differ in cell size, but should otherwise be comparable in order to be suitable as a model. We induced triploidy by cold shock and compared diploid and triploid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 77 publications
(89 reference statements)
3
24
0
Order By: Relevance
“…Across species or degrees of cell ploidy, cell size appears to be linked to the size of the nucleus, which in turn is linked to genome size, although the causality and its direction are not completely resolved (Gregory, 2001; Cavalier‐Smith, 2005; Hessen et al ., 2013). Indeed, artificially inducing triploidy in zebrafish ( Danio rerio ) resulted in a 50% increase in cell size, resembling the 50% increase in genome size (Van de Pol, Flik, & Verberk, 2020). Studies have found that plastic thermal responses in body size were accompanied by dynamic adjustments in both cell size and nucleus size (by adjusting chromatin packaging) and thus there is scope for cell size also to generate or parallel the TSR during ontogeny (Hermaniuk et al ., 2016; Leinaas et al ., 2016).…”
Section: The Dependency Of T–s Responses On Growth and Developmentmentioning
confidence: 97%
“…Across species or degrees of cell ploidy, cell size appears to be linked to the size of the nucleus, which in turn is linked to genome size, although the causality and its direction are not completely resolved (Gregory, 2001; Cavalier‐Smith, 2005; Hessen et al ., 2013). Indeed, artificially inducing triploidy in zebrafish ( Danio rerio ) resulted in a 50% increase in cell size, resembling the 50% increase in genome size (Van de Pol, Flik, & Verberk, 2020). Studies have found that plastic thermal responses in body size were accompanied by dynamic adjustments in both cell size and nucleus size (by adjusting chromatin packaging) and thus there is scope for cell size also to generate or parallel the TSR during ontogeny (Hermaniuk et al ., 2016; Leinaas et al ., 2016).…”
Section: The Dependency Of T–s Responses On Growth and Developmentmentioning
confidence: 97%
“…The utility of myofiber nuclear volume analysis for identifying triploids is clear, but this technique has produced some curious observations that are difficult to explain. Diploid embryos consistently have one tight peak of nuclear volumes and a second, smaller peak of nuclei that are approximately double the size (perhaps pre‐mitotic cells in the process of DNA replication as suggested in Van de Pol et al, 2020). While triploid embryos do produce a peak nuclear volume approximately 50% larger than that of diploids (as expected), the values are not normally distributed, extending into and below the modal volume of diploid embryos.…”
Section: Discussionmentioning
confidence: 77%
“…Mortality rates were similar between their heat‐treated triploids and our pressure‐treated triploids until 48 hpf, after which mortality rate improved greatly in pressure‐treated embryos (our study) but not in heat‐treated embryos (Delomas & Dabrowski, 2018). In contrast, survival of cold‐treated zebrafish embryos (71%; presumptive triploids) was not significantly different from controls (77%; presumptive diploids) at 24 hpf (Van de Pol et al, 2020) confirming that mortality is increased in the first 24 h regardless of the technique used to manipulate ploidy. We have shown that if a pressure‐treated triploid embryo survives beyond 24 hpf, they are likely to be viable, but we are unable to discern between the true effects of increasing ploidy and the effects of the physical treatments on embryo survival from our study.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations